2019
DOI: 10.3390/nano9081071
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Copper Nanoparticles with Photonic Additive for Printed Conductive Patterns by Intense Pulsed Light

Abstract: In this study, an ink formulation was developed to prepare conductive copper thin films with compact structure by using intense pulsed light (IPL) sintering. To improve inter-particle connections in the sintering process, a cuprous oxide shell was synthesized over copper nanoparticles (CuNP). This cuprous oxide shell can be reduced by IPL with the presence of a reductant and fused to form connection between large copper particles. However, the thermal yield stress after strong IPL sintering resulted in cracks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…It has been confirmed that the SiO 2 particles represent an elevation of about 50 to 90 nm and have a spherical shape. In order to apply SiO 2 ink to the ink-jet printing process, it has been reported that an average particle size of about 300 nm or less must be shown to prevent blockage in the print head nozzle; most of the SiO 2 particles used in this study showed uniform inlet and spherical shapes of less than 90 nm, which was judged to meet these requirements [ 20 , 21 , 22 ]. Figure 2 c shows the contact angle of the photo-curable nano SiO 2 ink on a hydrophobic-coated glass substrate using PFTS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that the SiO 2 particles represent an elevation of about 50 to 90 nm and have a spherical shape. In order to apply SiO 2 ink to the ink-jet printing process, it has been reported that an average particle size of about 300 nm or less must be shown to prevent blockage in the print head nozzle; most of the SiO 2 particles used in this study showed uniform inlet and spherical shapes of less than 90 nm, which was judged to meet these requirements [ 20 , 21 , 22 ]. Figure 2 c shows the contact angle of the photo-curable nano SiO 2 ink on a hydrophobic-coated glass substrate using PFTS.…”
Section: Resultsmentioning
confidence: 99%
“…Polyvinylpyrrolidone (PVP, Mw = 40,000g/mol, Sigma Aldrich, Munich, Germany) was added as a surface stabilizer and a reducing agent by sonication for 30 min. Then, ethanol (EtOH, 95%, Dae-Jung, Korea) and DEG (Diethylene glycol, 99%, Dae-Jung, Korea) were added to secure the printable and stirred at room temperature for 12 h [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our study shows that the Cu 2 O NPs with high absorbance in UV and short visible regions are most suitable to use the light energy for sintering because the semidehydro­ascorbic acid molecules absorbed on the Cu 2 O NPs play the role of self-reduction from Cu 2 O NPs to pure metallic Cu trace. Table compares the measured electrical resistivity from various types of conductive Cu traces with optimized processing conditions. …”
Section: Resultsmentioning
confidence: 99%
“…Cu oxide nanoparticles are more stable than their Cu nanoparticle counterparts. The IPL sintering can remove the oxide shells of Cu nanoparticles using the IPL-reactive protective agents, such as PVP, leaving a conductive Cu film in a short period of time (a few ms) under ambient conditions [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Ryu et al explained this phenomenon by oxide reduction either via an intermediate acid created by light irradiation or by hydroxyl (–OH) end groups, which act like long-chain alcohol reductants [ 100 ] ( Figure 11 ).…”
Section: Surface Designs By Surface Protective Layers Against the mentioning
confidence: 99%
“…Besides, the adhesion strength of the two-step sintered Cu ink film indicated a 5B level compared with that of a one-step sintered case of a 3B level. Chung et al used a mixed ink of Cu nanoparticles (~100 nm) with oxide shells of 20 nm and CuO nanoparticles (50 nm) for multiple IPL sintering to increase the light absorption efficiency and further decrease voids between Cu nanoparticles in the Cu film [ 106 ]. With an optimal Cu/CuO weight ratio of 1:80, the resistivity of the Cu film reduced as low as 6.5 μΩ·cm on PET, with the single energy at 3.08 J/cm 2 .…”
Section: Surface Designs By Surface Protective Layers Against the mentioning
confidence: 99%